In vitro toxic activity of Croton heliotropiifolius Kunth (Euphorbiaceae) - Silva, Jéssica de Andrade Gomes (2018)
Often found in some Brazilian biomas as caatinga, brejo, restinga and cerrado, the velame, Croton heliotropiifolius Kunth, is popularly known for its medicinal properties used in stomach ache, gastric reflux, vomiting, bloody diarrhea and to reduce fever. In addition to the pharmacological properties, its essential oil has larvicidal activity against Aedes aegypti, as well as the ethanol extract showed significant insecticidal activity against Sitophilus zeamais. This study aimed at evaluating the toxicity of preliminary methanolic extract of Croton heliotropiifolius Kunth on Artemia salina larvae. The bioassay was carried out at concentrations of 50 µg/ml, 100 µg/ml, 250 µg/ml, 500 µg/ml, 750 µg/ml, 1000 µg/ml of methanolic extract of leaves. The extract studied showed a moderate toxicity to Artemia salina, with LC 50 values in the range of 637,29 µg/mL.